Forty years of internalisation theory and the multinational enterprise. Issue 3 (19th August 2014) - Buckley, Peter; Rugman, Alan
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose The purpose of this paper is to review the key analytical principles of internalisation theory as a general theory of the multinational enterprise (MNE). It illustrates the vitality, relevance, and flexibility of the approach in explaining the continued evolution of the MNE. As a grounded social science theory, it provides, in combination with history and economic geography, satisfying and novel explanations of the key phenomena of the modern globalising economy. Design/methodology/approach This paper examines the origins and principles of internalisation theory as the foundation theory of the MNE. It considers internalisation theory in the context of current and mainstream theories and concepts in the field of international business. Findings Internalisation theory is equally valid for the MNEs of yesteryear as it is for those today. The theory continues to have strong explanatory power for MNE activity. Current research areas, such as multiple embeddedness, fine-slicing of the value chain, etc., and other theories, such as dynamic capabilities and the resource-based view, either are subsets of internalisation and thus explained by the theory, or contain weakness and/or inconsistencies not found in internalisation theory. Originality/value This paper coherently synthesises internalisation theory, its origins, and evolution. It shows how commonly-held and current concepts and theories are related to internalisation theory or have weaknesses, thus making internalisation theory a superior theory to explain the multinational enterprise, and identifies potential applications of the theory to novel research areas in the field of international business.